Virtual audits of streetscapes by crowdworkers. (September 2019) - Hanibuchi, Tomoya; Nakaya, Tomoki; Inoue, Shigeru
Abstract: Audits have been used to provide objective ratings of neighborhood environments. Physical audits, however, are time- and resource-intensive. This study examines the efficiency and reliability of virtual auditing using Google Street View and crowdsourcing to conduct walkability audits of streets in Japan. Overall, 830 street segments were physically and virtually audited by two trained auditors; 300 untrained crowdworkers also virtually audited 3 street segments. Statistical analysis found good inter-source and inter-rater reliability. This study helps establish crowdsourced virtual auditing as a valuable method of measuring neighborhood walkability, reducing audit costs as well as enabling large-scale auditor recruitment while maintaining reliability. Highlights: Audits of neighborhood streetscapes are time- and resource-intensive. Virtual audits using crowdsourcing reduce audit costs. Crowdworkers' audit scores showed good reliability. Crowdsourced virtual auditing is a valuable method to expand study areas.